Uruguay : Poverty Update 2003 - World Bank (Washington, DC, 2013)
After a decade of continuous growth, the Uruguayan economy experienced a recession over 1998-2001, with a deeper contraction registered in 2002 following the unraveling of the Argentinean crisis in late 2001, which culminated in default, and devaluation in early 2002. The recession had a deteriorating effect on poverty, and other social indicators, although considered better than in the majority of Latin American countries. Notably, increased unemployment began in 1998 - unemployment, and self-employment - was accompanied by a reduction in real wages in the private sector. In addition, since 1999, pensions, which constitute a sizeable portion of household incomes, have been falling as well. Vulnerable groups were the most affected, which are groups composed by households in which the head is unemployed, employed in the informal sector, or self-employed; crowded households; households headed by construction sector workers; and, by individuals with low educational attainment, or by young persons. There are also some "new poor", notably individuals living in households with intermediately educated heads. This growth in poverty resulted from three broad factors: a) higher incidence of unemployment, combined with longer unemployment spells, and less hours worked, all of which affected more the vulnerable segments; b) reductions in real earnings originated by inflation, and the reduced rate of increase in nominal remunerations. These were compounded by occupational, and sectoral shifts in the labor market, that contributed to the reduction of average earnings; and, c) higher household income inequality. The government response to the recession included many positive actions, in particular, the existence of a firmly established, and overall well designed set of social programs, including social assistance, and, there are three programs that play an important role in mitigating and coping with social risks: an early child development program; a housing program targeted to poor households in rural areas; and, a housing program with similar characteristics, but targeted to urban slums, introduced in 2000. Notwithstanding, some fragmentation within institutions, and overlapping program objectives across institutions, were found in some social interventions. A key question arising from the analysis in the Report is why nominal wages kept growing in the face of reduced economic activity, forcing a significant quantity adjustment of the labor market. Analyses of the effect of policies showed, that public wage rigidities exerted a negative, although small, impact on employment as a whole until 2001, especially for intermediately educated individuals, and those belonging to the three lowest quintiles of the income distribution. The report finds that both the public wage bill, and overall wage inequality would be lower if, public workers earned accordingly with the private pay structure. As noted in the final chapter, however, a deeper analysis of the labor market is needed, to assess other factors preventing adjustments in this market. Currently, the existing evidence in this regard is contradictory.